Pengaruh Bimbingan Kelompok dengan Teknik Sosiodrama dalam Mengurangi Kecemasan Berbicara di Depan Kelas Pada Siswa Kelas VII di SMP Negeri 10 Palembang - Argarini, Via; Gani, Syarifuddin; Putri, Rani Mega (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2019)
This study was aimed to find out the effect of group guidance with sosiodrama techniques in reducing anxiety speaking in front of the class in class VIIth grade students at SMP Negeri 10 Palembang. This study was experimental that used Pre-experimental design One Group PretestPosttest Design. The sample of this study was 8 students of VII th grade at SMP Negeri 10 Palembang who were selectedbased on purposive sampling technique with the sample criteria was students who had speaking anxiety in front of the class. The data collection used was speaking anxiety questionnaire. Based on the result of the data analysis, the significant level was 0,05, where =13.45 higher than = 2.365 which means was rejected and was accepted. The result of this study indicated that sociodrama techniques in group guidance services helped VII th grade students at SMP Negeri 10 Palembang to overcome their speaking anxiety in front of the class.